Therefore a Man Leaves His Father and His Mother and Clings to His Wife Marriage and Intermarriage in Genesis 2:24 - Warner, Megan (2017)
In recent decades the opponents of same-sex marriage have mounted a second front in the debate, shifting their focus from the so-called clobber texts to the creation narratives of Genesis. These scholars argue that Gen 2:24 presents a normative definition of marriage that precludes same-sex marriage. I argue that Gen 2:24 offers not a normative definition of the institution of marriage but a description of the powerful draw to relationship that is the result of God's actions in creation. Just as interpreters of Gen 2:24 across centuries and traditions have approached the verse against the background of a wide range of presenting social issues (e.g., divorce, incest, polygamy, bestiality, and, more recently, homosexuality), so the authors of Gen 2:24 were influenced by a pressing social issue, namely, intermarriage. I explore this hypothesis by means of a word study focusing on the verse's two verbs. The results of the word study are further tested by consideration of the historical and literary contexts of the verse and of the earliest instances of reuse of Gen 2:24 in canonical and noncanonical texts. I conclude that, far from presenting a normative definition of heterosexual marriage, Gen 2:24 is an acknowledgment of the powerful attraction that causes human beings to seek relationship in opposition to the wishes of their parents, society, and religion.
Keywords: Intermarriage; MARITAL statistics; Marriage; Polygamy; Same-sex marriage